Water-based low-zinc heat-resistant anticorrosive paint and preparation method thereof
By using fillers such as aluminum sheets, zinc oxide, titanium powder, etc. in the coating, combining low-melting point glass powder and conductive mica powder to form a physical barrier and electrochemical protective layer, the problem of insufficient heat resistance in high-temperature environments is solved, and a more efficient and environmentally friendly coating effect is achieved.
Patent Information
- Application Number
- CN202510397748.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-04-01
AI Technical Summary
Traditional high-zinc anticorrosion coatings are insufficient in high-temperature environments and are prone to peeling or degradation, affecting the durability of metal parts. At the same time, high zinc content poses a threat to the environment and workers' health.
Water-based low-zinc heat-resistant and anti-corrosion coating is used to replace part of the zinc powder by using fillers such as aluminum sheets, zinc oxide and titanium powder, and combining low-melting glass powder and conductive mica powder to form a dense physical barrier and electrochemical protective layer to improve the heat resistance and environmental friendliness of the coating.
It significantly improves the heat resistance of the coating, maintains stability in a high-temperature environment, prevents peeling and degradation, extends the protection time of metal substrates, and reduces the amount of zinc used, improves environmental compatibility and process flow, and reduces costs.
Smart Images

Figure CN119899550A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal corrosion and protection, and specifically relates to a water-based low-zinc heat-resistant anticorrosion coating and a preparation method thereof. Background Art
[0002] In the metal surface treatment industry, the main function of anti-corrosion coatings is to provide protection against corrosion and oxidation of metal substrates. Traditional anti-corrosion coatings usually contain a high content of zinc powder, which uses the cathodic protection properties of zinc to enhance the anti-corrosion ability. However, such high-zinc content coatings often face the problem of insufficient heat resistance in application environments such as high temperatures. Under these high-temperature conditions, the coating is prone to peeling, discoloration or degradation, which reduces the protective effect of the coating and thus affects the durability of metal parts. After the zinc powder content is reduced, the zinc oxide fume generated during welding / cutting is reduced by about 50%-70%. By adding conductive fibers / graphene, the utilization rate of zinc powder is increased by more than 30%, and the zinc consumption is reduced by 40% under the same protective effect. However, traditional high-zinc coatings produce a lot of zinc fume, which is easy to cause "zinc fever" and endanger the respiratory system of workers. The actual utilization rate of zinc powder is less than 50%, and a large amount of zinc powder is lost as the coating ages. Existing papers and other related reports show that the zinc powder content of traditional high-zinc paint accounts for 60%-80%, the welding zinc fume concentration is 5-8mg / m³, and the VOC content is 400-600g / L; the zinc powder content of low-zinc paint accounts for 20-40%; the welding zinc fume concentration is ≤2mg / m³, and the VOC content is 80-120g / L.
[0003] The disadvantage of the existing technical solutions is that although the high zinc coating can provide effective anti-corrosion protection, it performs poorly in dealing with high temperature effects and compatibility with other materials. At the same time, the stability of the coating under high temperature conditions is not ideal, which usually affects the protection effect of the coating-substrate interface. On the other hand, conventional low zinc content coatings are difficult to provide good cathodic protection function during the anti-corrosion process. Summary of the invention
[0004] In order to solve these problems, the present invention proposes a water-based low-zinc heat-resistant anticorrosive coating and a preparation method, which partially replaces zinc powder with fillers such as aluminum flakes, zinc oxide, and titanium powder, thereby significantly improving the heat resistance and environmental friendliness of the coating while ensuring anticorrosion performance, and meeting the needs of modern industry for high-performance coating materials. Through this innovative formula, the present invention aims to overcome the limitations of traditional technology, so that the coating can still maintain excellent protective performance in high-temperature environments such as workshops and industrial furnaces.
[0005] The technical solution of the present invention is: A water-based low-zinc heat-resistant anticorrosive coating, comprising the following components by mass percentage: Adhesive: lithium silicate adhesive 30%, lithium silicate 14%, sodium alginate 0.4%, distilled water 10%; Color fillers: Metal particles: Al flakes 0-4%, iron titanium powder 10%, zinc powder 16-18%; Non-metallic particles: zinc oxide 8%, conductive mica powder 0-4%, titanium dioxide 1%; Enamel filler: low melting point glass powder 2-4%; Additives: defoamer 0.2%, leveling agent 0.2%, dispersant 0.2%; The Al sheet is a floating aluminum sheet, and its surface is treated with hydrophobicity; The Al sheet and the conductive mica powder are used together in a ratio of 1:1; Low-melting-point glass powder and Al sheets form a dense physical barrier network structure; zinc powder serves as a sacrificial anode and conductive mica powder serves as an auxiliary conductor as an electrochemical protective layer.
[0006] Furthermore, in the above-mentioned water-based low-zinc heat-resistant anti-corrosion coating, the particle size of the zinc powder is 2000-800 μm.
[0007] Furthermore, in the above-mentioned water-based low-zinc heat-resistant anti-corrosion coating, the components of the low-melting point glass powder include, by mass percentage, 32% silicon dioxide, 18% boron oxide, 13% sodium oxide, 7% potassium oxide, 8% calcium oxide, 9% aluminum oxide, 10% ferrosoferric oxide, and 3% manganese oxide, and the glass softening point is 450-550°C.
[0008] A method for preparing a water-based low-zinc heat-resistant anticorrosive coating comprises the following steps: Step 1, sequentially stir and disperse distilled water, lithium silicate adhesive, and lithium silicate using a high-speed stirrer at a speed of 600-800 r / min for 8-10 minutes until uniform, to form a base material; Step 2, adding metal particles, non-metallic particles and enamel filler, using a high-speed mixer to stir and disperse at a speed of 400-500 r / min for 15-20 minutes, and mixing evenly to form a mixture; Step 3, add ground zirconium beads, and use a high-speed mixer to grind and disperse at a speed of 1800-2000 r / min for 0.5 h; Step 4, add additives and use distilled water to adjust the viscosity of the coating. Apply four cups at a flow rate of 20-30 seconds, and then filter the coating with a 250-mesh gauze to obtain the coating; Step 5: After spraying the coating onto the Q235 surface sample that has been sandblasted, the coating is cured at room temperature for 24 hours, and the total mass of zinc powder in the coating accounts for no more than 40% of the dry film weight.
[0009] Furthermore, in the above-mentioned method for preparing a water-based low-zinc heat-resistant anti-corrosion coating, the coating thickness obtained in step 5 is 40~50μm.
[0010] Furthermore, in the above-mentioned method for preparing a water-based low-zinc heat-resistant and anti-corrosion coating, the coating obtained in step 5 comprises a physical shielding layer and an electrochemical protective layer, wherein the physical shielding layer is a dense network structure composed of low-melting-point glass powder and Al sheets; and the electrochemical protective layer is zinc powder as a sacrificial anode and conductive mica powder as an auxiliary conductor.
[0011] Furthermore, the preparation method of the above-mentioned water-based low-zinc heat-resistant anti-corrosion coating, based on the synergistic effect of the physical shielding layer and the electrochemical protective layer, ensures that the coating does not powder or peel off at a high temperature of 400-600°C, and passes the GB / T 1771 and GB / T1740 tests.
[0012] The above-mentioned water-based low-zinc heat-resistant anti-corrosion coating is used in high-temperature, high-humidity and salt-containing environments in the fields of ships, chemical equipment and building materials.
[0013] Advantages and beneficial effects of the present invention: The water-based low-zinc heat-resistant anticorrosive coating of the present invention significantly improves heat resistance by using fillers such as aluminum flakes, zinc oxide and titanium powder to replace part of the zinc powder, so that the coating can maintain the stability of the coating in high-temperature environments such as workshops and industrial furnaces, prevent peeling and degradation, and thus extend the protection time of the metal substrate. At the same time, the low zinc content reduces the impact on the environment, meets environmental protection requirements, improves compatibility with non-metallic materials, simplifies the coating process and construction process, thereby improving construction efficiency and reducing costs, and ultimately provides a more efficient and environmentally friendly coating solution for modern industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a schematic diagram of the coating structure design of Example 3; Figure 2 This is the BSE diagram of the cross section of the sample in Example 3. DETAILED DESCRIPTION
[0015] The specific implementation modes of the present invention are described in further detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention but cannot be used to limit the scope of the present invention.
[0016] The present invention discloses a water-based low-zinc heat-resistant anticorrosive coating, which comprises the following components by mass percentage: Adhesive: lithium silicate adhesive 30%, lithium silicate 14%, sodium alginate 0.4%, distilled water 10%; Color fillers: Metal particles: Al flakes 0-4%, iron titanium powder 10%, zinc powder 16-18%; Non-metallic particles: zinc oxide 8%, conductive mica powder 0-4%, titanium dioxide 1%; Enamel filler: low melting point glass powder 2-4%; Additives: defoamer 0.2%, leveling agent 0.2%, dispersant 0.2%.
[0017] The Al sheet is a floating aluminum sheet, and its surface is treated with hydrophobicity.
[0018] Low-melting-point glass powder and Al sheets form a dense physical barrier network structure; zinc powder serves as a sacrificial anode and conductive mica powder serves as an auxiliary conductor as an electrochemical protective layer.
[0019] When the Al flakes and conductive mica powder are used together, the ratio is maintained at 1:1. This is because too high Al flake content will weaken the electrochemical protection properties of the coating, and too high conductive mica powder content will weaken the physical shielding protection properties of the coating. Maintaining a balanced ratio is more conducive to taking into account both anti-corrosion strategies.
[0020] The composition of the low-melting glass powder includes, by mass percentage, 32% silicon dioxide, 18% boron oxide, 13% sodium oxide, 7% potassium oxide, 8% calcium oxide, 9% aluminum oxide, 10% ferroferric oxide, and 3% manganese oxide, and its glass softening point is 450-550° C. The design of the glass softening point and composition is due to the application temperature of the coating design at 600° C. Therefore, it is necessary to ensure that the glass softening range of the low-melting glass powder is below 600° C., and the higher content of boron oxide, sodium oxide and potassium oxide and the lower content of aluminum oxide are helpful to reduce the glass softening point of the material.
[0021] Example 1. The present embodiment provides a water-based low-zinc heat-resistant anticorrosive coating, which comprises the following components by mass percentage: Adhesive: lithium silicate adhesive 30%, lithium silicate 14%, sodium alginate 0.4%, distilled water 10%; Color fillers: Metal particles: Al flakes 4%, iron titanium powder 10%, zinc powder 18%; Non-metallic particles: zinc oxide 8%, titanium dioxide 1%; Enamel filler: low melting point glass powder 4%; Additives: defoamer 0.2%, leveling agent 0.2%, dispersant 0.2%.
[0022] The zinc powder particle size is 2000 μm; The Al sheet is a floating aluminum sheet, and its surface is treated with hydrophobicity; The composition of the low-melting-point glass powder includes, by mass percentage, 32% silicon dioxide, 18% boron oxide, 13% sodium oxide, 7% potassium oxide, 8% calcium oxide, 9% aluminum oxide, 10% ferrosoferric oxide, and 3% manganese oxide, and the glass softening point is 450°C.
[0023] The preparation process of the water-based low-zinc heat-resistant anticorrosive coating comprises the following steps: (1) distilled water is heated to 95° C., sodium alginate is added as a dispersant and dispersed until dissolved, and lithium silicate binder and lithium silicate are added after natural cooling to room temperature, and a high-speed stirrer is used to stir and disperse at a speed of 800 r / min for 8 min until uniform; (2) Al flakes, iron titanium powder, zinc powder, zinc oxide, low melting point glass powder, and titanium dioxide were stirred and dispersed at a speed of 400 r / min for 15 min using a high-speed stirrer to form a mixture; (3) adding 50% of the total mass of the mixture of ground zirconium beads, and grinding and dispersing the mixture at a speed of 2000 r / min for 0.5 h using a high-speed mixer; (4) Add defoaming agent and leveling agent respectively, and use distilled water to adjust the viscosity of the coating. Apply four cups of coating at a flow rate of 26 seconds, and then use a 250-mesh gauze to filter the coating to obtain the coating.
[0024] (5) After the coating is sprayed onto the Q235 surface sample that has been sandblasted and cured at room temperature for 24 hours, the total mass of zinc powder in the coating accounts for no more than 40% of the dry film weight.
[0025] The coating thickness of this embodiment is about 40 μm. The prepared composite coating has a macroscopic morphology and a surface without obvious defects, and does not powder or peel off at a high temperature of 400° C.
[0026] Example 2. This embodiment is a water-based low-zinc heat-resistant anticorrosive coating, and its components are as follows by mass percentage: Adhesive: lithium silicate adhesive 30%, lithium silicate 14%, sodium alginate 0.4%, distilled water 10%; Color filler: Metal particles: 10% iron titanium powder, 18% zinc powder; Non-metallic particles: zinc oxide 8%, conductive mica powder 4%, titanium dioxide 1%; Enamel filler: low melting point glass powder 4%; Additives: defoamer 0.2%, leveling agent 0.2%, dispersant 0.2%.
[0027] The zinc powder particle size is 800 μm; The composition of the low-melting-point glass powder includes, by mass percentage, 32% silicon dioxide, 18% boron oxide, 13% sodium oxide, 7% potassium oxide, 8% calcium oxide, 9% aluminum oxide, 10% ferrosoferric oxide, and 3% manganese oxide, and the glass softening point is 550°C.
[0028] The preparation process of the water-based low-zinc heat-resistant anticorrosive coating comprises the following steps: (1) distilled water is heated to 95° C., sodium alginate is added as a dispersant and dispersed until dissolved, lithium silicate binder and lithium silicate are added after natural cooling to room temperature, and a high-speed stirrer is used to stir and disperse at a speed of 600 r / min for 8 min until uniform; (2) using a high-speed stirrer to stir and disperse iron titanium powder, zinc powder, zinc oxide, conductive mica powder, low-melting point glass powder, and titanium dioxide at a speed of 400 r / min for 20 min to form a mixture; (3) adding 50% of the total mass of the mixture of ground zirconium beads, and grinding and dispersing the mixture at a speed of 1800 r / min for 0.5 h using a high-speed mixer; (4) Add defoaming agent and leveling agent respectively, and use distilled water to adjust the viscosity of the coating. Apply four cups of water at a flow rate of 20 seconds, and then use a 250-mesh gauze to filter the coating to obtain the coating.
[0029] (5) After the coating is sprayed onto the Q235 surface sample that has been sandblasted and cured at room temperature for 24 hours, the total mass of zinc powder in the coating accounts for no more than 40% of the dry film weight.
[0030] The coating thickness of this embodiment is about 50 μm. The prepared composite coating has a dense structure, good bonding with the alloy interface, no obvious large hole defects, no cracks and other defects, and does not powder or peel off at a high temperature of 600°C.
[0031] Example 3. Adhesive: lithium silicate adhesive 30%, lithium silicate 14%, sodium alginate 0.4%, distilled water 10%; Color fillers: Metal particles: Al flakes 4%, iron titanium powder 10%, zinc powder 16%; Non-metallic particles: zinc oxide 8%, conductive mica powder 4%, titanium dioxide 1%; Enamel filler: low melting point glass powder 2%; Additives: defoamer 0.2%, leveling agent 0.2%, dispersant 0.2%.
[0032] The zinc powder particle size is 1200 μm; The Al sheet is a floating aluminum sheet, and its surface is treated with hydrophobicity; The composition of the low-melting-point glass powder includes, by mass percentage, 32% silicon dioxide, 18% boron oxide, 13% sodium oxide, 7% potassium oxide, 8% calcium oxide, 9% aluminum oxide, 10% ferrosoferric oxide, and 3% manganese oxide, and the glass softening point is 550°C.
[0033] The preparation process of the water-based low-zinc heat-resistant anticorrosive coating comprises the following steps: (1) distilled water is heated to 95° C., sodium alginate is added as a dispersant and dispersed until dissolved, and lithium silicate binder and lithium silicate are added after natural cooling to room temperature, and a high-speed stirrer is used to stir and disperse at a speed of 800 r / min for 10 min until uniform; (2) Al flakes, iron titanium powder, zinc powder, zinc oxide, conductive mica powder, low melting point glass powder, and titanium dioxide were stirred and dispersed at a speed of 500 r / min for 20 min using a high-speed stirrer to form a mixture; (3) adding 50% of the total mass of the mixture of ground zirconium beads, and grinding and dispersing the mixture at a speed of 1800 r / min for 0.5 h using a high-speed mixer; (4) Add defoaming agent and leveling agent respectively, and use distilled water to adjust the viscosity of the coating. Apply four cups of water at a flow rate of 30 seconds, and then use a 250-mesh gauze to filter the coating to obtain the coating.
[0034] (5) After the coating is sprayed onto the Q235 surface sample that has been sandblasted and cured at room temperature for 24 hours, the total mass of zinc powder in the coating accounts for no more than 40% of the dry film weight.
[0035] The schematic diagram of the coating structure of this embodiment is as follows Figure 1 As shown in the figure, the low-melting-point glass powder and Al flakes form a dense physical shielding network structure on the upper part of the coating, which provides a preliminary barrier to the corrosive medium; the zinc powder near the substrate side acts as a sacrificial anode and cooperates with the conductive mica powder as an electrochemical protective layer. This design enables the coating to have both chemical corrosion resistance and electrochemical corrosion resistance.
[0036] like Figure 2 The cross-sectional BSE diagram of the preparation state of this embodiment is shown. The coating thickness of this embodiment is about 50μm. The composite coating prepared in this embodiment has a dense structure, good bonding with the alloy interface, no obvious large hole defects, no cracks and other phenomena, and does not powder or peel off at a high temperature of 600°C. The top of the coating is the concentrated area of Al flakes, and the bottom is the concentrated area of zinc powder. This is because the Al flakes are floating aluminum flakes, and their surfaces have been hydrophobically treated. Therefore, during the curing process, they will tend to be at the top of the coating under the influence of buoyancy, and at the same time, they can reduce the penetration of water molecules and delay the hydrolysis aging of the coating; and zinc powder has a higher density than other fillers, so it tends to the bottom of the coating during the curing process. The structure shown in the figure is formed by one-time spraying using the physical and chemical properties of the filler itself.
[0037] Performance Test: The comparative example is the shop primer described in the specific implementation method of application number 202311527604.7, application date 2023.11.16, publication number CN117736592A, and name “A method for preparing ablation-resistant shop primer”.
[0038] The shop primers obtained in Examples 1-3 and the comparative example shop primers were subjected to performance tests, and the results are shown in Table 1: Table 1 Performance test results of examples and comparative examples
[0039] In the performance test results of Table 1, only the comparative example shows obvious color change, which is due to the good thermal stability of the filler of the modified coating and the low mass specific gravity of the high-temperature oxidation reaction. In corrosive environments such as humidity, heat, and salt spray, the embodiments all show obvious advantages, and the performance effect of embodiment 3 is the best, proving that this corrosion protection method combining physical shielding with chemical shielding has obvious advantages. Since the embodiment adds more low-melting-point glass powder than the comparative example, after a thermal shock of 600°C, the embodiment still shows good coating-substrate interface bonding, which is difficult to achieve in the comparative example.
Claims
1. A water-based low-zinc heat-resistant anticorrosive coating, characterized in that: The following components are included by mass percentage: Adhesive: lithium silicate adhesive 30%, lithium silicate 14%, sodium alginate 0.4%, distilled water 10%; Color fillers: Metal particles: Al flakes 0-4%, iron titanium powder 10%, zinc powder 16-18%; Non-metallic particles: zinc oxide 8%, conductive mica powder 0-4%, titanium dioxide 1%; Enamel filler: low melting point glass powder 2-4%; Additives: defoamer 0.2%, leveling agent 0.2%, dispersant 0.2%; The Al sheet is a floating aluminum sheet, and its surface is treated with hydrophobicity; The Al sheet and the conductive mica powder are used together in a ratio of 1:1; Low-melting-point glass powder and Al sheets form a dense physical barrier network structure; zinc powder serves as a sacrificial anode and conductive mica powder serves as an auxiliary conductor as an electrochemical protective layer.
2. A water-based low-zinc heat-resistant anticorrosive coating according to claim 1, characterized in that: The particle size of the zinc powder is 2000-800 μm.
3. A water-based low-zinc heat-resistant anticorrosive coating according to claim 1, characterized in that: The composition of the low-melting-point glass powder includes, by mass percentage, 32% silicon dioxide, 18% boron oxide, 13% sodium oxide, 7% potassium oxide, 8% calcium oxide, 9% aluminum oxide, 10% ferrosoferric oxide, and 3% manganese oxide, and the glass softening point is 450-550°C.
4. A method for preparing the water-based low-zinc heat-resistant anticorrosive coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, sequentially stir and disperse distilled water, lithium silicate adhesive, and lithium silicate using a high-speed stirrer at a speed of 600-800 r / min for 8-10 minutes until uniform, to form a base material; Step 2, adding metal particles, non-metallic particles and enamel filler, using a high-speed mixer to stir and disperse at a speed of 400-500 r / min for 15-20 minutes, and mixing evenly to form a mixture; Step 3, add ground zirconium beads, and use a high-speed mixer to grind and disperse at a speed of 1800-2000 r / min for 0.5 h; Step 4, add additives and use distilled water to adjust the viscosity of the coating. Apply four cups at a flow rate of 20-30 seconds, and then filter the coating with a 250-mesh gauze to obtain the coating; Step 5: After spraying the coating onto the Q235 surface sample that has been sandblasted, the coating is cured at room temperature for 24 hours, and the total mass of zinc powder in the resulting coating accounts for no more than 40% of the dry film weight.
5. The method for preparing a water-based low-zinc heat-resistant anticorrosive coating according to claim 4, characterized in that: The coating thickness obtained in step 5 is 40~50μm.
6. The method for preparing a water-based low-zinc heat-resistant anticorrosive coating according to claim 5, characterized in that: The coating obtained in step 5 comprises a physical shielding layer and an electrochemical protective layer. The physical shielding layer is a dense network structure composed of low-melting-point glass powder and Al sheets; the electrochemical protective layer is a sacrificial anode composed of zinc powder and conductive mica powder as an auxiliary conductor.
7. The method for preparing a water-based low-zinc heat-resistant anticorrosive coating according to claim 6, characterized in that: Due to the synergistic effect of the physical shielding layer and the electrochemical protective layer, the coating will not powder or peel off at high temperatures of 400-600°C, and pass the GB / T1771 and GB / T1740 tests.
8. Use of the water-based low-zinc heat-resistant anticorrosive coating according to claim 1 in a high-temperature, high-humidity, salt-containing environment in the fields of ships, chemical equipment, and building materials.
Citation Information
Patent Citations
Preparation method of ablation-resistant shop primer
CN117736592A
Aqueous inorganic zinc-enriched coating and preparation method thereof
CN101735674A
Light-colored waterborne anticorrosive antistatic coating for bottom and wall of storage tank and preparation method thereof
CN102993847A
High temperature resistant coating for engine exhaust system
CN103113768A
Water-based environment-friendly anti-corrosion composite material and preparation method thereof
CN110028816A